AUTOMATIC MOBILE OIL DISPENSING WITH MONITORING FOR TRAIN COMPRESSOR - Abad, Angelique Faith S.; Bañola, Kian M.; Evangelista, Raniel Adam D.; Gimeno, Johnloid S.; Reyes, Gerald P.; Ballesteros, Mariezol; Garcia, Julius G.; Delizo, Carlo Jay G.; Bunag, Sherlie D.; Sison, Venerando A.; Andador, Jennifer D. (IC-ITECHS, 2024)
Train compressors require the appropriate oil level to function effectively. Kettles and pitchers are useless, inexact, and dangerous for hand oil replenishment. To solve these problems, this project developed an automated mobile oil delivery system that monitored the oil. The technology avoids spills, dispenses oil accurately, and monitors oil levels and battery efficiency in real-time. All of the above requires a very thoughtful design and development of a self-priming pump, ultrasonic sensors, an electronic battery sensor, an ultrasonic flow meter, and an Arduino Giga display. It was developed and tested locally. The system accurately administered oil and monitored oil levels and the condition of the battery; excellent comments were received from the maintenance experts. This implies that automated oil refilling for railway depots' train compressor oil may enhance efficiency and safety. The potential to work with various train compressors, as well as economic and environmental advantages, deserve further research.